Productivity growth improves in housefurnishings industry. - Critchlow, Robert (Monthly Labor Review, 1996)
Following periods of decline, productivity in the housefurnishings industry increased steadily after 1980. The housefurnishings industry is made up of about 1,000 businesses dominated by a fairly small number of large companies, and its most important products are bedroom and bathroom fabrics such as pillowcases, bedsheets, comforters, bath towels, and other similar textile goods. Large and medium-sized companies led the pace of the industry's productivity growth with restructuring, plant consolidations, and technological advances. Factors such as sound marketing strategies and growing consumer demand also contributed to the industry's progress. The writer discusses employment and earnings, job skills and training, and operations and technology in the housefurnishings industry.